ANALYSIS OF GOOD GOVERNANCE IN CIPAKU VILLAGE GOVERNMENT MREBET DISTRICT, PURBALINGGA DISTRICT - Putri Puja Lasenda; Taufik Purboyo; Oti Kusumaningsih (Department of Public Administration, University Wijaykusuma Purwokerto, 2023)
This research is entitled